Pendampingan Belajar Operasi Hitung Aljabar di SMP Kristen 03 Kalabahi Kelas VII - Elen Abigail Hinadang; Jon Idrison Molina; Jeni Marianti Loban; Yuliana Adriyanti Mowata; Marta Outang (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The service activities carried out are in the form of learning assistance in mathematics for class VII students at Christian Middle School 03 Kalabahi, the purpose of this mentoring activity is to increase students' understanding, enthusiasm and enthusiasm for learning, especially in mathematics subject material about arithmetic operations algebraic form. Class VII students of SMP Kristen 03 Kalabahi have low interest in mathematics, this can be seen from their lack of enthusiasm in learning in class and their low understanding of the material provided. This is known through observation and initial identification carried out in class. This mentoring activity is carried out through teaching and learning assistance to students using test methods, lectures, discussions and problem solving methods. At the beginning of this mentoring activity, students gave pretest with the aim of being able to find out the abilities of students before carrying out mentoring. After being provided with assistance by the service team, the students will be given posttest with the aim of knowing the level of success of the assistance carried out. The results of this activity have a very good and enthusiastic response from students to take part in good tutoring which can increase students' understanding, enthusiasm and enthusiasm in learning algebraic arithmetic operations.